Um imperador cristão merece o céu: a construção de memórias sobre o imperador Graciano nos escritos de Ambrósio (séc. IV d.C.) - Pohlmann, Janira Feliciano [UNESP] (Universidade Estadual Paulista Julio de Mesquita Filho, 2020)
Ambrose found in Gratian the first emperor who offered him an official public space for the defence of the Christian-Nicene belief. This new space went beyond episcopal preaching and texts about the question of the female virginity debated by the priest. That is why, through his writings, the Milanese bishop transformed Gratian into a holy emperor, protector of the Nicene. In this work, my purpose is to examine the memory created by Ambrose about the place of Gratian in the heaven, a discursive construction that moved away the august of the traditional divine apotheosis. This analysis will be made on the basis of two Ambrosian’s funeral laudations: De Obitu Valentiniani Consolatio (392 AD) and De Obitu Theodosii Oratio (395 AD).

Ambrósio encontrou em Graciano o primeiro imperador que lhe ofereceu um espaço público oficial para a defesa da crença cristã-nicena. Este novo espaço ia além das pregações episcopais e dos textos sobre a questão da virgindade feminina debatida pelo sacerdote. Por isso, através de seus escritos, o bispo milanês transformou Graciano em um “santo imperador”, protetor dos nicenos. Neste trabalho, meu objetivo é examinar a memória criada por Ambrósio sobre o lugar de Graciano no céu, uma construção discursiva que afastava o augusto da tradicional apoteose divina. Tal análise será feita com base, especialmente, em duas laudações fúnebres de autoria ambrosiana: De Obitu Valentiniani Consolatio (de 392) e De Obitu Theodosii Oratio (de 395).
A Christian Emperor Deserves Heaven: The Building of Memories of Emperor Gratian in the Writings of Ambrose (4th Century AD)
Keywords: Emperor Gratian; Memory; Death; Imperador Graciano; Memória; Morte